A Custom Firmware and Lightweight Battery System Design for Portable RFID Reader - Trio Adiono; Hans Kasan; Suksmandhira Harimurti; Farkhad Ihsan Hariadi (JURNAL INFOTEL, 2018)
Small to large-scale companies mostly have warehouses to store their inventories, and to manage them a warehouse management system is required. A low cost, yet powerful solution is using a portable RFID reader. In RFID portable reader system, there are three components which are the most essential, i.e. host and its firmware, RF module, and battery.. In this paper, we propose a custom firmware design, which is compatible with different RFID reader chips or development boards. The custom firmware is designed to work by triggering the execution of Electronic Product Code (EPC) Generation 2 protocol standard command on the reader chip. Hence, the firmware can fully utilize the reader chip’s command. Furthermore, a lightweight battery system is also designed. Targeting for a high mobility use, a very lightweight Li-Pro battery, weighing of only 0.1 kg, is used for the battery system. It is also able to work at long operating hour up to 4 hours.